Balancing Growth and Sustainability: Developing a Socio-ecological Urban Design Framework for Edge Cities - Goutham J.S.; Sruthi Satheesan (International Journal of Urban Design and Development, 2026)
In the rapidly urbanizing world, edge cities, urban areas situated on the outskirts of larger metropolitan regions have emerged as dynamic centres of economic activity. However, their development often prioritizes growth over sustainability, leading to ecological degradation and social inequities. This dissertation presents a socio-ecological urban design framework aimed at balancing growth with sustainability in edge cities. By integrating principles from ecology, sociology, and urban planning, this framework addresses the challenges of environmental sustainability, equitable social development, and resilient infrastructure. Using case studies of selected edge cities, the research identifies key factors influencing the interplay between rapid urbanization, ecological health, and community well-being. The findings propose guidelines and policy recommendations to guide the future development of edge cities, ensuring they contribute positively to the environment and society while maintaining their role as economic hubs. In conclusion, this research underscores the urgent need to reimagine edge cities through a socio-ecological lens that balances economic ambition with environmental responsibility and social equity. As these peripheral urban areas continue to expand, their long-term viability will depend on integrated planning approaches that recognize the interdependence between natural systems, built environments, and community life. By proposing actionable design strategies and policy frameworks, this dissertation contributes to a more sustainable and inclusive model of edge city development. Ultimately, it positions edge cities not just as fragmented by-products of metropolitan growth, but as transformative urban territories capable of fostering resilience, ecological regeneration, and collective well-being in the face of rapid urban change. Additionally, the study highlights that embedding socio-ecological principles into early planning decisions is essential to ensure that future edge city growth is adaptive, regenerative, and socially inclusive rather than reactive and environmentally extractive.
Keywords: Edge cities; Environmental concern; social inclusivity; socio-ecological urban design; spatial analysis; urbanization